2014
DOI: 10.1007/s00405-014-2902-0
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy in routine tonsillectomy specimens: a systematic literature review

Abstract: The aim of this systematic literature review was to investigate the prevalence of unsuspected tonsillar malignancy in routine tonsillectomy specimens and to discuss whether histological examination is indicated in tonsillectomy specimens from patients without well-defined risk factors. PRISMA 2009 guidelines were considered and applied whenever possible. Articles on prevalence of unsuspected tonsillar malignancy in routine tonsillectomy specimens were selected. Unsuspected tonsillar malignancy was defined as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…In a recent review, unsuspected tonsillar malignancy was found in three out of 6,434 adult patients (prevalence 0.05 %) because of routine histological examination of the tonsils. One of these patients presented with PTA and another had a history of recurrent PTA [3]. In agreement with other researchers, the possibility of PTA as an independent risk factor for tonsillar malignancy was questioned [1,3,10].…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…In a recent review, unsuspected tonsillar malignancy was found in three out of 6,434 adult patients (prevalence 0.05 %) because of routine histological examination of the tonsils. One of these patients presented with PTA and another had a history of recurrent PTA [3]. In agreement with other researchers, the possibility of PTA as an independent risk factor for tonsillar malignancy was questioned [1,3,10].…”
Section: Introductionmentioning
confidence: 72%
“…Unsuspected tonsillar malignancy, diagnosed by coincidence because of routine histological examination, is infrequently found in patients presenting with peritonsillar abscess (PTA) [3,[5][6][7][8][9][10][11]. In a recent review, unsuspected tonsillar malignancy was found in three out of 6,434 adult patients (prevalence 0.05 %) because of routine histological examination of the tonsils.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations